Semantic and functional features of tauromachy (bullfighting) vocabulary within the framework of cognitive and linguoculturological approaches - Aliyeva, Aytan (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article is dedicated to the investigation and interpretation of semantic and functional features of phraseological expressions and paroemias referring to tauromachy (bullfighting) within the framework of cognitive and linguoculturological approaches. The introduction of relevant examples in the article aims to detect these features. Tauromachy which is called "an art of bullfighting" is an inseparable part of Spanish culture. Corrida (bullfight) has deep historical roots and it is a specific, festive occasion belonging to the Spanish people. It has entered into the national consciousness of Spaniards, developed and reflected in all manifestation forms of their lives. In its turn, it has lead to the linguistic reflection of tauromachy vocabulary in the language. According to their use in the language, tauromachy terms have four levels: words referring to tauromachy which is a special field and used only in the bullfight, tauromachy words with figurative meaning that can be used as a methaphora in other fields, tauromachy words used in literature and words referring to tauromachy field used in spoken language. Linguoculturological approach is a new stage of the study of complex relations between language, thinking and culture within the framework of cognitive linguistics. Linguistic and semantic aspects of cognitivism, that’s, mental imaginations of a language speaker are observed more vividly in phraseological expressions and paroemias. In the article we will try to study phraseological expressions and paroemias referring to tauromachy used in the spoken language, that’s, the fourth level of the use of tauromachy vocabulary in the language. It is obvious that the phraseological system generalizes language units with extremely great value in terms of understanding the level of national language consciousness of the people. Phraseological expressions and paroemias can be considered precious linguoculturological source, so that daily lifestyle, world outlook, traditions of language speakers are reflected in the phraseological system visually through metaphoric coding. The vocabulary of tauromachy in this field has gone through certain processes and gained new connotative meanings and assists in more concrete, laconic, expressive delivery of the idea being used in the spoken language.
Keywords: cognitive linguistics, linguoculturology, tauromachy, phraseological units, paroemias.